Newborn Dried Blood Spots for Serologic Surveys of COVID-19 - Liu, Feimei (Pediatr Infect Dis J, 2020)
There is an urgent need for inexpensive, population-wide surveillance testing for COVID-19. We tested newborn dried blood spot (DBS) anti-SARS-CoV-2 antibodies for all infants born at Yale from March to May 2020, and found that newborn DBS serologies reflect maternal and population-wide infection rates during the study period. This suggests a role for DBS in COVID-19 surveillance in areas where viral testing is limited.